KARAKTERISTIK MINUMAN ISOTONIK BERBAHAN BAKU AIR KELAPA DAN MADU PADA PENYIMPANAN DINGIN - Nur Izzah Az-zahra; Giyarto Giyarto; Maryanto Maryanto (Berkala Ilmiah Pertanian, 2019)
The coconut water has been declared a natural isotonic drink because it a fairly complete minerals. However, coconut water is easily damaged and polluted by the activity of microorganisms, so effort to improve the stability of coconut water is needed. Honey is a natural food source that has a function as a taste, contains rich minerals, and as an antimicrobials is expected to inhibit the growth of microorganisms as a solution in extending the shelf life of coconut water. With this ability, honey can be added (fortified) to the isotonic drink of coconut water. This research aims to measure the quality characteristics of isotonic drinks made from coconut water with variations of honey concentration during cold storage. The stages of this research was carried out with the preparation of the ingredients, the preparation of isotonic beverages according to the treatment, and the testing of quality characteristics during cold storage. Isotonic drinking stage made of coconut water and honey (100 ml Hydro coco as control (P0); 95 mL coconut water: 5 mL of honey (P1); 92.5 mL coconut water: 7 mL honey (P2), 90 mL coconut water: 10 mL honey (P3), 87.5 mL coconut water: 12.5 mL honey (P4), and 85 mL coconut water: 15 mL of honey (P5)). Measurement of quality characteristics (content of Na, K, ash, and degree of acidity) isotonic drinks of honey coconut water every 10 days once a month periodically. The results data are presented in tables and graphs, and analyzed descriptively. The results showed that the value of Na and K content in each sample was between 85.79-102.44 ppm and 1860.1-2020,8 ppm, the value of ash content in the lowest sample was 1.9681% and the highest was 4.7448 %, and the lowest degree of acidity (pH) was 3.4 and the highest was 5.7.Keywords: isotonic drinks, coconut water, honey Air kelapa telah dinyatakan sebagai minuman isotonik alami karena mengandung mineral yang cukup lengkap. Namun, air kelapa mudah rusak dan mudah tercemar oleh aktivitas mikroorganisme, sehingga upaya untuk meningkatkan stabilitas air kelapa sangat dibutuhkan. Madu merupakan sumber makanan alami yang memiliki fungsi sebagai rasa, mengandung mineral yang kaya, dan antimikroba diharapkan dapat menghambat pertumbuhan mikroorganisme sebagai solusi dalam memperpanjang stabilitas air kelapa. Dengan kemampuan ini, madu dapat ditambahkan (fortifikasi) ke minuman isotonik air kelapa. Penelitian ini bertujuan untuk mengukur kualitas karakteristik minuman isotonik yang dibuat dari air kelapa dengan variasi konsentrasi madu selama penyimpanan dingin. Tahapan penelitian ini dilakukan dengan persiapan bahan, pembuatan minuman isotonik sesuai perlakuan, dan pengujian karakteristik kualitas selama penyimpanan dingin. Tahapan pembuatan minuman isotonik yang terbuat dari air kelapa dan madu (100 ml Hydro coco sebagai kontrol (P0); 95 mL air kelapa: 5 mL madu (P1); 92,5 mL air kelapa: 7 mL madu (P2 ), 90 mL air kelapa: 10 mL madu (P3), 87,5 mL air kelapa: 12,5 mL madu (P4), dan 85 mL air kelapa: 15 mL madu (P5)). Pengujian karakteristik kualitas (kandungan Na, K, abu, dan derajat keasaman) minuman isotonik madu air kelapa setiap 10 hari sekali selama sebulan secara berkala. Data hasil disajikan dalam bentuk tabel dan grafik, dan dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa nilai kadar Na dan K pada masing-masing sampel adalah antara 85,79-102,44 ppm dan 1860,1-2020,8 ppm, nilai kadar abu pada sampel terendah adalah 1,9681% dan tertinggi 4,7448%, dan nilai derajat keasaman (pH) terendah adalah 3,4 dan tertinggi 5,7. Kata Kunci : Minuman isotonic, Air Kelapa, Madu